2006
DOI: 10.1007/s10072-006-0711-y
|View full text |Cite
|
Sign up to set email alerts
|

Leukoencephalopathy as a rare complication of hepatitis C infection

Abstract: We report the case of a 64-year-old female patient with hepatitis C infection (HCV), who developed Sjögren's disease and sensory peripheral neuropathy. Clinical conditions worsened over three years with central nervous system involvement characterised by transient third cranial nerve paresis and mild selective impairment of attention and memory. Brain magnetic resonance imaging showed diffuse periventricular and lobar white matter hyperintensity. Laboratory findings included mixed cryoglobulinaemia (type II), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…A total of 279 patients (30 from our department and 249 from the literature search) 2 9 , 11 , 12 , 15 19 , 24 , 25 , 27 , 32 , 33 , 35 , 36 , 38 , 39 , 42 52 , 54 , 55 , 59 75 , 81 , 82 , 84 – 86 , 89 , 91 95 , 98 – 100 fulfilled the inclusion criteria (Table 1 ). There were 146 (52%) female patients and 133 (48%) male, with a mean age at diagnosis of cryoglobulinemia of 54 years (range, 25–87 yr) and a mean age at life-threatening involvement of 55 years (range, 25–87 yr).…”
Section: Resultsmentioning
confidence: 99%
“…A total of 279 patients (30 from our department and 249 from the literature search) 2 9 , 11 , 12 , 15 19 , 24 , 25 , 27 , 32 , 33 , 35 , 36 , 38 , 39 , 42 52 , 54 , 55 , 59 75 , 81 , 82 , 84 – 86 , 89 , 91 95 , 98 – 100 fulfilled the inclusion criteria (Table 1 ). There were 146 (52%) female patients and 133 (48%) male, with a mean age at diagnosis of cryoglobulinemia of 54 years (range, 25–87 yr) and a mean age at life-threatening involvement of 55 years (range, 25–87 yr).…”
Section: Resultsmentioning
confidence: 99%
“…The neuropathological examination of this patient has shown multiple ischemic lesions (0.53 mm in diameter) in the white matter of cerebral hemis pheres, cerebellum, parenchymal infiltration, and an accumulation of the lymphocytes around small vessels. Further study has also shown the incidence of vasculitis induced ischemic changes in a patient that was suffering with chronic HCV, MC, and sensory neuropathy [56] . Besides the encephalopathic syndromes, cognitive decline that has been clinically characterized by an impaired attention, visual constructive, and spatial functions have been associated with an enhanced occurrence of periventricular white matter high intensity signals (WMHISs) on T2weighted MRI [56] .…”
Section: Mechanisms Contributing To Neurological Dysfunctionmentioning
confidence: 97%
“…Further study has also shown the incidence of vasculitis induced ischemic changes in a patient that was suffering with chronic HCV, MC, and sensory neuropathy [56] . Besides the encephalopathic syndromes, cognitive decline that has been clinically characterized by an impaired attention, visual constructive, and spatial functions have been associated with an enhanced occurrence of periventricular white matter high intensity signals (WMHISs) on T2weighted MRI [56] . The patients have shown a relationship between CG level and number of impaired cognitive functions whereas no correlation was observed with systemic manifestations of CG, including peripheral neuropathy.…”
Section: Mechanisms Contributing To Neurological Dysfunctionmentioning
confidence: 97%
“…Pathological evidence of CNS vasculitis-induced ischemic damage was first provided in a patient with MC, peripheral neuropathy, and relapsing multiinfarct encephalopathy [17]; in this case, neuropathological examination showed multiple ischemic lesions, 0.5–3 mm in diameter, in the white matter of cerebral hemispheres and cerebellum, and parenchymal infiltration and accumulation of lymphocytes around small vessels. The occurrence of possible vasculitis-induced ischemic changes has been also claimed in a patient with chronic HCV infection, MC, Sjögren syndrome, and sensory neuropathy, who developed skin vasculitis and leukoencephalopathy over a three-year period [18]. Taken together, these reports suggest that active HCV infection can be responsible for acute/subacute white-matter involvement, when associated with CG, coagulation disorders, or systemic vasculitis.…”
Section: Neurological Manifestationsmentioning
confidence: 79%